MEASURING THE EFFECT OF MACROECONOMIC VARIABLES ON THE STOCK MARKET RETURN: EVIDENCE FROM CHITTAGONG STOCK EXCHANGE - Chowdhury, Emon Kalya (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
It is very important for policymakers to understand the impact of macroeconomic variables on the stock market return to formulate appropriate policies for the socio-economic development of a country. This paper attempts to find the impact of macroeconomic factors like inflation rate, interest rate, money supply, unemployment rate risk premium, and exchange rate on the return of stocks listed on the Chittagong Stock Exchange. Arbitrage Pricing Theory (APT)is used considering monthly data of different factors viz., inflation rate, interest rate, money supply, unemployment rate, risk premium, and exchange rate in Bangladesh from 2005 to 2014. Durbin Watson statistics are applied to examine the nature of autocorrelation among data series. Ordinary Least Square method is applied and it finds a substantial pricing linkage between selected macroeconomic factors and stock return. The weak correlations among the selective factors indicate that other macroeconomic variables influence stock market return in CSE.